(untitled) (Global Journal of Science Frontier Research, 2024)
Our aim in this paper is to study the well-posedness results of anisotropic conservative Caginalp phasefield system based on the theory of type III thermomechanics with two temperatures for the heat conduction and periodic boundary conditions More precisely we prove the existence and uniqueness of solutions